Etiology and Immediate Outcome of Neonatal Convulsions : A Hospital Based Study - Haque, Salina; Hossain, Shahadat; Datta, Mitra; Quader, Mohammed Maruf Ul (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Neonatal seizures are the most common manifestation ofneurological disorders in the newborn period and an important determinant ofoutcome To evaluate the causes and immediate outcome in hospital of neonatalconvulsions. Materials and methods: This hospital based prospective study was conducted inSpecial Care Neonatal Unit (SCANU) Department of Paediatrics and Child HealthBangabandhu Memorial Hospital (BBMH) USTC, including 30 neonates sufferingfrom convulsion from 1 to 28 days of age during the period of 1st July to 30thOctober, 2003. Results: Twenty-four (80%) cases were under 5 days age, 4 (13.33%) cases wereranged 6 to 15 days age. The mean age of the patients was 3 days. 18 (60%)babies were male and 12 (40%) were female. Male:female ratio was 1.5:1.Twenty (66.67%) babies had normal body weight (2500-4000 g). Maternalcomplications during pregnancy were present in 10 (33.33%) cases. Convulsionwas present in all 30 (100%) cases. Depressed primitive reflexes were found 16(53.33%) cases, cyanosis in 5 (16.67%) cases, fever in 7 (23.33%) cases. Subtleseizures were present in 16 (53.33%) cases, focal clonic and focal tonic seizureswere present in 7 (23.33%) and 4 (13.33%) cases, respectively. Generalized tonicseizures were present in 3 (10%) cases and none (0%) cases had myoclonicseizure. Onset of convulsion in relation to age revealed that 13 (43.33%) caseshad convulsion before 24 hours of age, 10 (33.33%) developed convulsionbetween 1-3 days of age, 5 (16.67%) and 2 (6.67%) had convulsion between 4-7days and 8-21 days of age respectively. Commonest cause of neonatalconvulsion was found to be Hypoxic-Ischaemic Encephalopathy (HIE). It wasfound in 17 (56.67%) patients. Hypoglycaemia as primary metabolic cause wasfound in 4 (13.33%) patients, and septicaemia was found in 3 (10%) patients.Eighteen (60%) cases stayed in hospital for 7-10 days, out of which 16 (53.33%)were cured and 2 (6.67%) died. Three (10%) cases stayed in hospital for 4-5days, all of them were cured, Two (6.67%) cases stayed in hospital for 3 daysand among them 1 (3.33%) died and another was cured and discharged onrequest. Five cases (16.67%) stayed for 11-14 days in hospital, out of them 3(10%) were cured and 2 (6.67%) expired. Only 1 case (3.33%) stayed for morethan 14 days and died at day 20. The mortality rate in this study is 20%. Conclusion: The most common cause of neonatal seizure was HIE (56.67%).Other causes of neonatal convulsions are septicaemia, meningitis, primarymetabolic disorders like hypoglycaemia and hypocalcaemia, intraventricularhaemorrhage and some causes are still unknown. Mortality due to neonatalconvulsion is still very high, and in this series, it was found to be 20 percent.Survival while staying in hospital occurred in 24 (80%) cases. Chatt Maa Shi Hosp Med Coll J; Vol.19 (1); January 2020; Page 8-14